Georg Herbert Mead: contribuições para a Psicologia Social - Souza, Renato Ferreira de (2006)
The developed work intends to contribute for the understanding of an author/character of the social psychology. We analyzed and we added knowledge about George Herbert Mead and the unfoldings of his psychosocial theory. For this purpose we worked in two basic pathways: first, through the social approach of the psychology s history, we confronted Mead s life with moments of constitution of the psychology at his time, placing in projection central aspects of his dialogue not always identified. We correlated the history of Mead with social subjects, politics, economical and scientific of his time; information on what happened in the plan of the interpersonal s relationships at the time he was elaborating his theory, as well as his connections with practices and specific cultural values were mediated. The second path elapses from an incursion that goes through a thematic concerning to the Meadelian s studies, for what we prioritized the sociologists Peter Berger s and Thomas Luckmann s works and of the philosopher Jürgen Habermas. It is then intended to contribute to the history of the social psychology and to diffuse the Meadelian s scientific concepts, turning them more accessible to the specialists of the social psychology